KAJIAN SITUS GUNUNG DEZH DI PULAU SALAWATI (Study of Dezh Mountain Site in Salawati Island) - Fairyo, Klementin (BALAI ARKEOLOGI PAPUA, 2014)
Dezh Mountain site is the site occupancy of Japanese colonial period in Kampung Solol, Salawati, where the site of Mount Dezh describe Japan’s political strategy in the control of Papua. As for the archaeological remains found on this site in the form of foundation of the house, ceramic fragments, and fragments bicycle rim. Other archaeological findings were found in the location of Kampung Solol are tools factory. This research was conducted with the aim of knowing the forms of archaeological remains on the site of Mount Dezh and know the function of the archaeological remains. The method used in this study is the observation, literature and interviews ABSTRAKSitus Gunung Dezh adalah situs hunian masa kolonial Jepang di Kampung Solol, Pulau Salawati, keberadaan situs Gunung Dezh menggambarkan strategi politik Jepang dalam menguasai Papua. adapun tinggalan arkeologi yang ditemukan pada situs ini berupa fondasi rumah, fragmen keramik, dan fragmen pelek sepeda. Temuan arkelogi lainnya yang ditemukan di lokasi Kampung Solol adalah alat-alat pabrik. Penelitian ini dilakukan dengan tujuan mengetahui bentuk-bentuk tinggalan arkeologi di situs Gunung Dezh dan mengetahui fungsi dari tinggalan arkeologi tersebut. Metode yang digunakan dalam penelitian ini adalah observasi lapangan, studi pustaka dan wawancara.